Probiotics as Alternative Therapy for Psychometric Disorders in Hepatic Encephalopathy - Bany Faris Amin; Irfan Kresnadi; Vannessa Karenina; GM Yudi Prasetia A; Trivani Putri; Juferdy Kurniawan (The Indonesian Society for Digestive Endoscopy, 2019)
Aim: To identify whether probiotics have the same effectiveness as lactulose in improving the results of psychometric testing in patients with hepatic encephalopathy.Method: Literature Searching were performed on Pubmed, EBSCOhost, Scopus, and Cochrane databases to obtain an randomized controlled trial (RCT) or a systematic review. Searches were made with the keywords